Sex differences in disease-specific health status measures in patients with symptomatic peripheral artery disease: Data from the PORTRAIT study. (April 2017) - Roumia, Mazen; Aronow, Herbert D; Soukas, Peter; Gosch, Kensey; Smolderen, Kim G; Spertus, John A; Abbott, J Dawn
Peripheral artery disease (PAD) is associated with poor health status (symptoms, functioning, quality of life (QOL)). Whether sex differences exist in PAD-specific health status is unknown. In patients presenting to a specialty clinic with new-onset or recent exacerbation of PAD, we examined sex differences as assessed by the Peripheral Artery Questionnaire (PAQ). The Patient-centered Outcomes Related to TReatment Practices in Peripheral Arterial Disease: Investigating Trajectories (PORTRAIT) study is a multicenter, international prospective study of patients with new or worsening PAD symptoms. Baseline characteristics and mean PAQ scores were compared among women ( n =481) and men ( n =793) before they underwent treatment. The independent association of sex with health status was assessed with multivariable linear regression. As compared with men, women were less often Caucasian, married and employed, and more often lacking health insurance, living alone (36.2% vs 23.6%, p <0.001), had depression and avoided care due to cost (17.0% vs 12.3%, p =0.018). Women and men were of a similar age and education level, and had similar ankle–brachial index (ABI) values (0.7 ± 0.2 in both groups, p =0.052). Female sex was independently associated with lower PAQ scores on all domains (physical functioning adjusted mean difference of −8.40, p <0.001; social functioning adjusted mean difference of −6.8, p <0.001; QOL adjusted mean difference of −6.7, p <0.001), although no differences were observed in treatment satisfaction (adjusted mean difference −0.20, p =0.904). Despite similar ABIs, women presenting with symptoms of PAD had poorer PAD-specific functioning as compared with men, impacting all major health status domains, independent of socio-economic and clinical characteristics.